Community-based coastal resource management as a contributor to sustainability-seeking communities : a case study for Ísafjörður, Iceland - Landry, Jamie Elizabeth (2011)
There is an increasing demand from public, private, and government sectors for a coastal resource management regime that ensures sustainability of coastal natural resources while meeting local needs of the people it serves. It is the objective of this master's thesis to explore the suitability of Community-Based Coastal Resource Management (CBCRM) as a contributor to meeting the specific sustainability goals of the Icelandic coastal town of Ísafjörður. While focusing on the local needs of a specific community, CBCRM encourages a participatory role in the sustainable management of their coastal resources for groups and individuals. The research in this thesis aims to evaluate how CBCRM can and cannot contribute to Ísafjörður's sustainability goals by using a combination of research methods. Data representing pre-determined indicators of sustainability was collected while primary research methods included individual interviews held with a cross-section of community members. Additionally, a feasibility study exploring the suitability of CBCRM as a contributor to the town's sustainability goals was conducted. This feasibility study compared components of CBCRM with the specific sustainability goals of Ísafjörður and results showed that CBCRM was well suited to contribute to environmental sustainability goals in Ísafjörður. The feasibility study also revealed that CBCRM has the potential to positively contribute to certain economic and socio-cultural goals however several challenges were identified regarding these two sectors. Recommendations include utilizing the methods and principles of CBCRM to work towards several sustainability goals while continuing to use principles of Integrated Coastal Zone Management (ICZM) in order to achieve a holistic approach that meets the town´s needs.